Colorectal cancer after negative colonoscopy in fecal immunochemical test-positive participants from a colorectal cancer screening program - Rivero-Sánchez, Liseth; Grau, Jaume; Augé, Josep María; Moreno, Lorena; Pozo, Angels; Serradesanferm, Anna; Díaz, Mireia; Carballal, Sabela; Sánchez, Ariadna; Moreira, Leticia; Balaguer, Francesc; Pellisé, Maria; Castells, Antoni; on behalf of the PROCOLON group (Endoscopy International Open, 2018)
Background and study aims Colorectal cancer (CRC) risk after a positive fecal immunochemical test (FIT) and negative colonoscopy is unknown. We aimed to ascertain the cumulative incidence of post-colonoscopy colorectal cancer (PCCRC) and the manifestation of other lesions that could explain the test positivity in individuals with a negative colonoscopy in a population screening program.Patients and method Observational study in participants from the first round of a CRC screening program (2010 – 2012) with positive-FIT (≥ 20 μg/g of feces) and negative colonoscopy (without neoplasia). A 42- to 76-month follow-up was performed searching in the National Health Service database and by a brief structured telephonic interview.Results Of 2659 FIT-positive individuals who underwent colonoscopy, 811 (30.5 %) had a negative colonoscopy. Three PCCRC (0.4 %) were detected within 11 – 28 months and accelerated carcinogenesis was ruled out. Among those with normal colonoscopy, 32 (5 %) relevant lesions were detected at follow-up. One-third of them (11/32) were significant neoplasias: a gastric cancer, a small-bowel lymphoma, six advanced colorectal adenomas, and the three PCCRC. The 21 remaining lesions were inflammatory, vascular disorders, or non-advanced colorectal adenomas.Conclusions The vast majority (95 %) of individuals did not present any subsequent lesion that could explain the FIT positivity. The very low incidence (0.4 %) and characteristics of PCCRC observed in our cohort reinforce the concept that, although a positive FIT preselects high risk individuals, a high quality colonoscopy is the paramount factor in preventing PCCRC. Improving quality standards of colonoscopy are required to strengthen the current CRC screening strategies.